Konstruksi Sosial Keterlibatan Ayah dalam Pengasuhan Anak di Keluarga - Asti Lestari; Siti Komariah; Puspita Wulandari1 (Dimensia: Jurnal Kajian Sosiologi, 2026)
This study explores the gap between expectations and the reality of fathers’ roles in child-rearing in Indonesia. Although awareness of the importance of fathers’ involvement has increased, its implementation still faces various structural, cultural, and personal barriers. Using a qualitative approach with a phenomenological design, this study involved three fathers with children aged 0–18 years in Bandung. Data were collected through in-depth semi-structured interviews. The findings indicate that fathers’ perceptions of the importance of involvement in child-rearing have improved; however, the division of roles remains largely traditional, with mothers positioned as the primary caregivers. Major challenges include work-related demands, limited parenting knowledge, a lack of family-friendly policies, and persistent social stigma. From the perspective of Berger and Luckmann’s social construction theory, this phenomenon suggests that gender roles in child-rearing are socially constructed and can be transformed through policy interventions, educational programs, and shifts in societal paradigms